Familiar JAK2 G571S Variant Not Linked with Essential Trombocythemia - Panovska Stavridis, Irina; Eftimov, Aleksandar; Pivkova Veljanovska, Aleksandra; Ivanovski, Martin; Chevrevska, Lidija; Dimovski, Aleksandar (American Society of Hematology, 2014)
Abstract Somatic activating mutations in the JAK2 gene are one of the most important characteristics of the myeloproliferative neoplasams (MPNs). Moreover, JAK2 germline mutations occur in familiar MPN. However, the same JAK2 mutations are associated with different phenotypic MPNs and their exact role in the pathogenesis of the MPNs is not clear and well established. Here, we report a family with a germline JAK2 G571S mutation associated with only one sporadic case of essential thrombocythaemia (ET). Our patient, male, born 1958, presented at the age of 54 with a marked and sustained thrombocythosis (platelets count higher than 1500x109per liter over a period of 3 months). The bone marrow biopsy sample revealed normocellular bone marrow with an increased number of megakaryocytes organized in clusters; the reticulin staining was negative. The molecular diagnostic work up towards MPNs included the analysis of BCR/ABL fusion transcript, JAK2, CALR and MPL mutations. These analyses showed that the patient had 2 variants which might account for the ET phenotype; a somatic CARL mutation (insertion p.K385fs*47) and a germline C-T substitution at codon 571 in exon 13 of the JAK2 gene. Extended family analysis showed that the G571 variant was also present in the patient’s father, brother and one daughter. All of them had normal hematological parameters and didn’t exhibit any abnormality in the serum ferritin, prolactin, lipids, fasting glucose levels, blood pressure, body mass index, skin and skeletal changes. The JAK2 G571S mutation was already described in MPNs with a frequency <0.01 and was not recorded in the database of single nucleotide polymorphisam (SNP). Glycine at 571 is adjacent to Tyr570 which is one of the most important sites for autophosphorilation and downregulation of JAK2 signaling. The substitution of nonpolar Glycine for polar but non-charged Serine might affect this by altering the conformation of the protein and result in a constitutively active kinase. However, the absence of any hematological or other disorders in a wide age spectrum in carriers of this variant indicate that it is a silent nonfunctional polymorphism. Moreover, the ET phenotype present in the index case is reminiscent of other ET patients with somatic CALR p.K385fs*47 mutation, further demonstrating that the JAK2G571 variant is a non-functional silent polymorphism. Our results support the need for routine screening for all mutations that might be involved in the pathogenesis of the MPNs since they are not always mutually exclusive and also not always responsible for the phenotypic expression of the MPNs. Disclosures No relevant conflicts of interest to declare.